STUDENTS RESPONSES TOWARD ANIMATION VIDEO IN SPEAKING CLASS - Arip Naksa Bandi; Acep Haryudin (IKIP Siliwangi, 2022)
Speaking has important role in real life situation because related with oral communication activity, based on that situation teacher should give the best treatment and set the appropriate condition where the students have a big opportunity to learn what students need which is speaking ability. The Research activity was conducted at Kabupaten Bandung in one of the senior high schools, with 27 students of tenth grade as a subject of the research. This article shows the implementation of animation video in speaking class with the aim to know the student's responses after receiving the treatment. The research employed descriptive qualitative research as a way to show the result of the research. The result also shows the responses of students after receiving the animation video as media of learning activity, through observation sheet result, the table of students’ responses toward animation video and the description from interview activity. Keywords: Animation Video, Speaking